2016
DOI: 10.1111/adj.12395
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of traumatic dental injuries: a review of the literature

Abstract: Dental trauma is a significant public health problem because of its frequency, impact on economic productivity and quality of life. It is not a disease and no individual is ever at zero risk of sustaining these potentially life-changing injuries. The aim of this article was to review the literature on the prevalence, incidence, aetiology, prognosis and outcomes of dental trauma. The importance of standardized reporting, oral health policy, adjunctive research methods, prevention and education will also be disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
336
0
41

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(457 citation statements)
references
References 85 publications
25
336
0
41
Order By: Relevance
“…In terms of etiology, falls were the most common cause of TDI. It was in line with several other reports (1,6,8,14).…”
Section: Akyıldız Et Al Dental Trauma Of Children In Aydınsupporting
confidence: 94%
See 3 more Smart Citations
“…In terms of etiology, falls were the most common cause of TDI. It was in line with several other reports (1,6,8,14).…”
Section: Akyıldız Et Al Dental Trauma Of Children In Aydınsupporting
confidence: 94%
“…In agreement with many investigations, it was found that the most common injured teeth were maxillary central incisors (1,8,(11)(12)(13)(14)(15)(16)20,24). This might be associated with the position of these teeth, which exposes them to direct traumatic force.…”
Section: Akyıldız Et Al Dental Trauma Of Children In Aydınsupporting
confidence: 86%
See 2 more Smart Citations
“…Traumatic dental injuries are prevalent in primary as well as in permanent dentition with the maxillary anterior teeth being the most commonly affected area [1]. Crown-root fractures account for 5% of all dental injuries affecting the permanent teeth.…”
Section: Introductionmentioning
confidence: 99%